Adult care providers' perspectives on the transition to adult care for emerging adults with Type 1 diabetes: a cross‐sectional survey. Issue 7 (2nd May 2018) - Michaud, S.; Dasgupta, K.; Bell, L.; Yale, J.‐F.; Anjachak, N.; Wafa, S.; Nakhla, M.
Abstract: Aims: To assess adult diabetes care providers' current transition practices, knowledge about transition care, and perceived barriers to implementation of best practices in transition care for emerging adults with Type 1 diabetes mellitus. Methods: We administered a 38‐item web‐based survey to adult diabetes care providers identified through the Québec Endocrinologist Medical Association and Diabetes Québec. Results: Fifty‐three physicians responded (35%). Fewer than half of all respondents (46%) were familiar with the American Diabetes Association's transition care position statement. Approximately one‐third of respondents reported a gap of >6 months between paediatric and adult diabetes care. Most (83%) believed communication with the paediatric team was adequate; however, only 56% reported receiving a medical summary and 2% a psychosocial summary from the paediatric provider. Respondents believed that the paediatric team should improve emerging adults' preparation for transition care by developing their self‐management skills and improve teaching about the differences between paediatric and adult‐oriented care. Only 31% had a system for identifying emerging adults lost to follow‐up in adult care. Perceived barriers included difficulty accessing psychosocial services, emerging adults' lack of motivation, and inadequate transition preparation. Most (87%) were interested in having additional resources, including a self‐care management tool and a registry to track those lost to follow‐up. Conclusions: Our findings highlight the need to better engage adult care providers into transition care practices. Despite adult physicians' interest in transition care, implementation of transition care recommendations and resources in clinical care remains limited. Enhanced efforts are needed to improve access to mental health services within the adult healthcare setting. What's new?: Adult healthcare providers play a pivotal role in integrating emerging adults into the adult healthcare setting, but knowledge of the transition care practices and perspectives of the adult diabetes care provider remain limited. Our findings highlight the need to improve communication between paediatric and adult care providers and better engage adult healthcare providers into transition care practices so as to support the emerging adult through the transition process. Increased efforts to improve access to mental health services within the adult healthcare setting are needed.